What are thin capitalization tax schemes and how are they being countered by policy makers. - Jón Bjarni Steinsson 1981- (2015)
An examination of how multinational corporations use thin capitalization in order to avoid taxation and move profits across borders by providing an overview of the rules put in place to counter such behaviors and international steps being taken to further battle profit shifting as a way of tax avoidance. Finally, an explanation of their affects and how or if such rules should be implemented in Iceland where multinational corporations seem to be taking an advantage of such rules to avoid paying any income tax. Óheimilt er að afrita verkefnið að hluta eða í heild án leyfis höfundar hverju sinni.